Implementasi Pembelajaran Lintas Budaya dalam Perspektif Pengajar BIPA: Tantangan dan Peluang - Ananda Siti Khoirunnisa; Yaya Sunarya (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
BIPA learning can adapt the concept of intercultural learning with the aim of mastering language and understanding Indonesian culture. Intercultural learning bridge the process of introducing Indonesian culture in the BIPA class. The success of a learning process does not escape the challenges and opportunities faced by teachers. This study aims to describe the challenges and opportunities of intercultural learning from the perspective of BIPA teachers. The research method used is descriptive-qualitative. Researchers interviewed the research subjects, who were six BIPA teachers. The results showed that there were several challenges and opportunities in BIPA intercultural learning. Some challenges in intercultural learning are differences in perspective and cultural background, self-adaptation, heterogeneous class situations, cultural similarities seek, and learner needs. Some of the opportunities for these challenges, namely intercultural communication, intercultural discussion, and Indonesian culture diplomacy. Furthermore, this research can be a reference for BIPA teachers in implementing intercultural learning.